A Not Obvious Correlation Between the Structure of Green Fluorescent Protein Chromophore Pocket and Hydrogen Bond Dynamics: A Choreography From ab initio Molecular Dynamics - Coppola, Federico; Perrella, Fulvio; Petrone, Alessio; Donati, Greta; Rega, Nadia (Frontiers in Molecular Biosciences, 2020)
The Green Fluorescent Protein (GFP) is a widely studied chemical system both for its large amount of applications and the complexity of the excited state proton transfer responsible of the change in the protonation state of the chromophore. A detailed investigation on the structure of the chromophore environment and the influence of chromophore form (either neutral or anionic) on it is of crucial importance to understand how these factors could potentially influence the protein function. In this study, we perform a detailed computational investigation based on the analysis of ab-initio molecular dynamics simulations, to disentangle the main structural quantities determining the fine balance in the chromophore environment. We found that specific hydrogen bonds interactions directly involving the chromophore (or not), are correlated to quantities such as the volume of the cavity in which the chromophore is embedded and that it is importantly affected by the chromophore protonation state. The cross-correlation analysis performed on some of these hydrogen bonds and the cavity volume, demonstrates a direct correlation among them and we also identified the ones specifically involved in this correlation. We also found that specific interactions among residues far in the space are correlated, demonstrating the complexity of the chromophore environment and that many structural quantities have to be taken into account to properly describe and understand the main factors tuning the active site of the protein. From an overall evaluation of the results obtained in this work, it is shown that the residues which a priori are perceived to be spectators play instead an important role in both influencing the chromophore environment (cavity volume) and its dynamics (cross-correlations among spatially distant residues).